Book of abstracts of the 1st International Scientific Conference Teaching Methods for Economics and Business Sciences, (8 May 2017, Maribor, Slovenia) (University of Maribor Press, 2017)
Teaching is a challenging yet rewarding profession which is underpinned by one essential question: how do we build a good teaching and learning environment so that our students can acquire professional competences which will enable them to be successful in today’s global business environment. This book presents the abstracts of the 1st International Scientific Conference »Teaching Methods for Economics and Business Sciences« held on 8 May 2017 at the University of Maribor, Faculty of Economics and Business. I would like to thank all authors who submitted their work for this conference in our common search for the answer to the above question.